Functional properties of a recombinant bacterial DING protein: Comparison with a homologous human protein - Scott, K.; Wu, L.
DING proteins are highly-conserved proteins with poorly-defined cell-signalling roles in mammals. Conserved homologues are also commonplace in plants, though not as yet functionally characterized. Poor availability of the proteins, and a lack of genetic structure, hamper progress in elucidating the roles of these eukaryotic DING proteins, but highly-homologous hypothetical DING proteins have recently been identified in Pseudomonas genomes. We have cloned and expressed a DING protein from P. fluorescens SWB25 in Escherichia coli. The recombinant protein, and its natural human homologue, act as phosphate-binding proteins, as predicted by structural homologies with other bacterial proteins. The recombinant protein also displays other functional similarities with mammalian DING proteins, in that, like the human version, it acts as a mitogen for cultured human cells, and can bind cotinine, known to be a binding ligand for a rat neuronal DING protein.
Keywords: DING PROTEIN; CELL-SIGNALING; PSEUDOMONAS FLUORESCENS; HUMAN; MITOGEN; PHOSPHATE-BINDING